Author Correction: The 8-bromobaicalein inhibited the replication of dengue, and Zika viruses and targeted the dengue polymerase (Scientific Reports, (2023), 13, 1, (4891), 10.1038/s41598-023-32049-x) - Boonyasuppayakorn, S (Springer Science and Business Media LLC, 2023)
10.1038/s41598-023-34883-5